The Effect of Benzo (A) Pyrene on Glutathione Transferase and Glutathione Peroxidase in Mice Mus musculus Liver - Parichehr, Hanachi; N.A, Shamaan; J, Ramli; J.H, Arshad; M.A, Syed (Malaysian Journal of Science, 2003)
The dose response of two enzymes (glutathione S-transferase and glutathione peroxidase) involved in BaP metabolism and the amounts of BaP were evaluated in an experiment with mice Mus musculus. Thirty mice were divided into five groups. The first group of mice acted as control while the remaining four groups were injected once intraperitoneally with one of four doses of BaP (100, 150, 200 and 250 mg/kg) and sampled at two weeks after exposure. All of the doses studied caused significant induction in body weight compared to the control. On the other hand, no significant differences were observed on liver weight and liver/body weight ratio between the treated and control. The cytosolic glutathione-S-transferase activity (GST) significantly increased with 100 to 250mg/kg and glutathione peroxidase activity marked increase with 100 to 200 mg/kg dose of BaP. GST activity significantly increased with dose after exposure, while glutathione peroxidase activities reached a maximum and remained at a plateau at a dose 200 mg/kg BaP. It is concluded that GST activity provide a much more sensitive method than GPx activity to monitor recent exposure to BaP in mice.The dose response of two enzymes (glutathione S-transferase and glutathione peroxidase) involved in BaP metabolism and the amounts of BaP were evaluated in an experiment with mice Mus musculus. Thirty mice were divided into five groups. The first group of mice acted as control while the remaining four groups were injected once intraperitoneally with one of four doses of BaP (100, 150, 200 and 250 mg/kg) and sampled at two weeks after exposure. All of the doses studied caused significant induction in body weight compared to the control. On the other hand, no significant differences were observed on liver weight and liver/body weight ratio between the treated and control. The cytosolic glutathione-S-transferase activity (GST) significantly increased with 100 to 250mg/kg and glutathione peroxidase activity marked increase with 100 to 200 mg/kg dose of BaP. GST activity significantly increased with dose after exposure, while glutathione peroxidase activities reached a maximum and remained at a plateau at a dose 200 mg/kg BaP. It is concluded that GST activity provide a much more sensitive method than GPx activity to monitor recent exposure to BaP in mice.The dose response of two enzymes (glutathione S-transferase and glutathione peroxidase) involved in BaP metabolism and the amounts of BaP were evaluated in an experiment with mice Mus musculus. Thirty mice were divided into five groups. The first group of mice acted as control while the remaining four groups were injected once intraperitoneally with one of four doses of BaP (100, 150, 200 and 250 mg/kg) and sampled at two weeks after exposure. All of the doses studied caused significant induction in body weight compared to the control. On the other hand, no significant differences were observed on liver weight and liver/body weight ratio between the treated and control. The cytosolic glutathione-S-transferase activity (GST) significantly increased with 100 to 250mg/kg and glutathione peroxidase activity marked increase with 100 to 200 mg/kg dose of BaP. GST activity significantly increased with dose after exposure, while glutathione peroxidase activities reached a maximum and remained at a plateau at a dose 200 mg/kg BaP. It is concluded that GST activity provide a much more sensitive method than GPx activity to monitor recent exposure to BaP in mice.